COMPLICATIONS OF THE SUDEP (SUDDEN UNEXPECTED DEATH IN EPILEPSY) DISCUSSION. Issue 11 (9th October 2013) - Ng, Yi Shiau; Davenport, Richard; Duncan, Susan; Derry, Christopher
Abstract : Introduction: Sudden unexpected death in epilepsy (SUDEP) is a challenging issue for neurologists and many remain uncertain about if and when to discuss this with patients. Some advocacy groups have campaigned for early discussion of SUDEP after diagnosis in all, and the importance of such a discussion is emphasised in national guidelines. However, robust data to support this approach is lacking, and little is known of any negative impact of such discussions. We highlight an adverse outcome from early discussion of SUDEP in one patient. Case description: A 37 year old female presented following two unprovoked generalised tonic–clonic seizures within 3 weeks. She had a previous diagnosis of idiopathic generalised epilepsy in childhood, but treatment had been discontinued at the age of 8 and she had remained seizure free for many years. She had no psychiatric history. A diagnosis of recurrent epilepsy was made, investigations arranged and Levetiracetam commenced. The risk of SUDEP was discussed during the initial consultation. Subsequently, standard EEG and MRI head were normal. A month later, on Levetiracetam 1.5g daily, she reported frequent, new attacks which were different to the tonic–clonic seizures with which she had presented. These attacks were associated with features of panic and dissociation, suggestive of psychogenic non–epileptic attacks. It transpired that the patient and her family had become extremely worried after they were told about SUDEP and believed that she was 'living on borrowed time'. The patient had been under supervision by family members continuously since the first consultation, her husband giving up his job to facilitate this. She was admitted for videotelemetry which confirmed the new attacks were non–epileptic. After an explanation of the nature of the attacks, and reassurance about the low risk of SUDEP, the attacks improved. Discussion: To date, the mechanism of SUDEP remains largely unknown and evidence–based preventative measures are lacking. The frequency of generalised tonic–clonic seizures appears to be the dominant risk factor, and it has been suggested that early discussion of SUDEP may encourage adherence to treatment, thus reducing seizure frequency and hence the risk of SUDEP. However, it seems likely that such discussions may have negative psycho–social effects in some individuals, such as our patient. It is important to consider the timing, nature and content of such discussions, and to be sensitive to possible psycho–social harm that may result from them. More detailed studies of the impact of early SUDEP discussion are required.